Application of jigsaw type cooperative learning to student learning outcomes in class ix SMP Negeri 2 Ngabang - Emiliya, Emiliya; Erikson, Soni; Arianto, Dimas Paulus; Florida, Radha; Almahdi, Arif (PT The Collaboration UVW, 2023)
This research aimed to find out: the average student learning outcomes before being given the Jigsaw-type cooperative learning model affect student learning outcomes, the average student learning outcomes after being given the model Jigsaw type cooperative learning on student learning outcomes, and to determine the effect of implementing the Jigsaw type cooperative learning model on student learning outcomes in the introduction of hardware and software material in class IX of SMP Negeri 2 Ngabang. The independent variable was the Jigsaw-type cooperative learning model, while the related variable was learning outcomes. In this research, researchers used experimental research methods, a quasi-experimental design research form with a nonequivalent control group design. The population in this research was all students in class IX of SMP Negeri 2 Ngabang, Landak Regency, totaling 233 students. The sampling technique used was purposive sampling. Data collection techniques used measurement techniques. The data analysis technique from the results of this research was the t-test. The results that were known after conducting this research were that there was a significant interaction effect between the use of the Jigsaw-type cooperative learning model on student learning outcomes. The average score of student learning outcomes using the Jigsaw learning model was higher than the average score of student learning outcomes using the conventional learning model (lecture), there was a significant difference in learning outcomes between those taught using the Jigsaw cooperative learning model and the conventional learning model (lecture).